Ganges in crystal structure of fullerene films at alloying and radiation defect formation - Dmytrenko, O.P.; Kulish, N.P.; Prylutskyy, Yu.I.; Grabovskiy, Yu.E.; Pavlenko, E.L.; Poroshin, V.G.; Rodionova, T.V.; Poperenko, L.V.; Stashchuk, V.S.; Shlapatskaya, V.V.; Scharff, P. (Functional Materials, 2006)
The crystal structure of the C₆₀ fullerene films with their alloying by the oxygen molecules and copper atoms in studied and under the influence of high energy eletron irradiation (Ee = 1.8 MeV) is investigated. It is shown that the crystal structure of the C₆₀ and C₇₀ films changes in the dependence on the concentration of impurity elements and radiation damages substantially infuluences the electronic and vibration spectra of fullerenes and is the result of the appearance in this case of additional Coulomb intermolecular interaction.